Low Skilled Immigration and Work-Fertility Tradeoffs Among High Skilled US Natives - Furtado, Delia; Hock, Heinrich (American Economic Review, 2010)
Low Skilled Immigration and Work-Fertility Tradeoffs among High Skilled US Natives by Delia Furtado and Heinrich Hock. Published in volume 100, issue 2, pages 224-28 of American Economic Review, May 2010